Oral Health Status of Elderly People Living in Different Old Homes of Karachi - Mohsin Haider; Muhammad Arqam Najmi; Kulsoom Fatima Rizvi; Maria Moin; Syed Ahmed Omer; Arsalan Khalid; Fareha Sajjad; Rabbiya Imtiaz (Journal of Aziz Fatimah Medical and Dental College)
ABSTRACT Objective: To assess the oral health status of elderly people living in Karachi based old home.